2016
DOI: 10.1175/bams-d-14-00106.1
|View full text |Cite
|
Sign up to set email alerts
|

The “Pause” in Global Warming: Turning a Routine Fluctuation into a Problem for Science

Abstract: There has been much recent published research about a putative “pause” or “hiatus” in global warming. We show that there are frequent fluctuations in the rate of warming around a longer-term warming trend, and that there is no evidence that identifies the recent period as unique or particularly unusual. In confirmation, we show that the notion of a pause in warming is considered to be misleading in a blind expert test. Nonetheless, the most recent fluctuation about the longer-term trend has been regarded by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 59 publications
2
68
0
3
Order By: Relevance
“…Based on the results shown in Figures e–h and , the DM component was in a cooling phase during 2000–2010, which offset the long‐term warming trend and caused the warming hiatus (Huang et al , ). The “warming hiatus” is just a decadal climate fluctuation or perturbation, as illustrated in recent studies (Lewandowsky et al , ). Since 2013, the DM component has entered a warming phase; this is evident from the global, land, and ocean surface temperature time series.…”
Section: Discussion On the Future Evolution Of The Warming Hiatusmentioning
confidence: 93%
“…Based on the results shown in Figures e–h and , the DM component was in a cooling phase during 2000–2010, which offset the long‐term warming trend and caused the warming hiatus (Huang et al , ). The “warming hiatus” is just a decadal climate fluctuation or perturbation, as illustrated in recent studies (Lewandowsky et al , ). Since 2013, the DM component has entered a warming phase; this is evident from the global, land, and ocean surface temperature time series.…”
Section: Discussion On the Future Evolution Of The Warming Hiatusmentioning
confidence: 93%
“…Does it imply that the slowdown never really existed? Recent papers have analyzed unfiltered global temperature series and have concluded that the recent slowdown was either an artefact of the data or that it never really happened (Foster and Rahmstorf, 2011;Karl et al, 2015;Cahill et al, 2015;Lewandowsky et al, 2015Lewandowsky et al, , 2016. A large part of the body of research on this topic has concluded that the apparent hiatus could be produced by the effects of low-frequency natural variability represented by physical modes such as AMO, NAO and PDO (Li et al, 2013;Trenberth and Fasullo, 2013;Steinman et al, 2015;Guan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of globally average surface temperatures over the period 1998 to 2012/2014 has attracted a great deal of attention, with questions being raised as to whether the observed values represented a serious hiatus (or pause) in global warming or whether they simply corresponded to a decadal-scale fluctuation associated with internal variability of the climate system (Lewandowsky et al 2015(Lewandowsky et al , 2016. The Intergovernmental Panel on Climate Change (IPCC 2013;Flato et al 2013) concluded that a reduction of the warming trend (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) was attributable, in roughly equal measure, to a cooling contribution from both internal climate variability, and external forcing comprising solar and volcanic activity.…”
Section: Introductionmentioning
confidence: 99%